Students take the lead for learning in practice: A process for building self-efficacy into undergraduate nursing education. (July 2018) - Henderson, Amanda; Harrison, Penny; Rowe, Jennifer; Edwards, Sam; Barnes, Margaret; Henderson, Simon; Henderson, Amanda
Abstract: To prepare graduate nurses for practice, the curriculum and pedagogy need to facilitate student engagement, active learning and the development of self-efficacy. This pilot project describes and explores an initiative, the Check-in and Check-out process, that aims to engage students as active partners in their learning and teaching in their clinical preparation for practice. Three interdependent elements make up the process: a check-in (briefing) part; a clinical practice part, which supports students as they engage in their learning and practise clinical skills; and a check-out (debriefing) part. A student evaluation of this initiative confirmed the value of the process, which has subsequently been embedded in the preparation for practice and work-integrated learning courses in the undergraduate nursing programs at the participating university. The introduction of a singular learning process provides consistency in the learning approach used across clinical learning spaces, irrespective of their location or focus. A consistent learning process—including a common language that easily transfers across all clinical courses and clinical settings—arguably enhances the students' learning experience, helps them to actively manage their preparation for clinical practice and to develop self-efficacy. Highlights: The curriculum needs to be structured to foster inquiry by nursing students. Enhanced inquiry can improve students' understanding because they identify knowledge gaps. A single, consistent learning process might build student self-efficacy in various clinical learning spaces.